FAKTOR-FAKTOR YANG MEMENGARUHI INFLASI INTI DI INDONESIA - Christianingrum, Ratna; Syafri, Riza Aditya (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
Inflation is an important macroeconomic indicator. High inflation can reduce real income, which means there is a decrease in purchasing power. The level and volatility of Indonesia’s inflation have been higher compared with the trend in emerging markets and developing countries. This research is conducted to analyze the influence of fuel price, interest rate, GDP, gold price, IPI, exchange rate, and money supply on the core inflation rate in Indonesia. Data analysis was done using Vector Error Correction Models (VECM). The results show that in the short run, GDP, IPI, exchange rate, and money supply have a significant effect on the core inflation rate. In the long run, fuel prices, GDP, and exchange rates have significant effects on the core inflation rate in Indonesia.